Efektivitas Penggunaan Media Diorama dalam Meningkatkan Pemahaman Konsep Bentuk-Bentuk Bentang Alam Wilayah Daratan pada Siswa Kelas IV Sekolah Dasar : Penelitian - Khalashinikov, Stela Ramadhani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the effectiveness of using diorama media in improving the understanding of the concept of landforms in fourth grade elementary school students. The population in the study were all fourth grade students of Barongan Kudus Second Elementary School. Sampling in the study used a purposive sampling technique. The instrument in the study used a test instrument by giving pretest and posttest questions to students. The data analysis technique used statistical testing in the SPSS paired sample t-test application. Based on the test results, it explains that there is a statistically significant increase between the pretest and posttest scores with a t-count value of 18.35 and an N-gain effectiveness level of 0.616 (moderate category). The paired sample t-test df is 29. The t-count is 18.35, the t-table is 2.045, and the 2-tailed sig is 0.000. The data distribution shows that the calculated t-value > from the t-table of 18.35 > 2.045 and the 2-tailed sig value 0,000 < 0.05, so Ho = rejected and Ha = accepted. This indicates a significant difference between the results of the pretest and posttest data values.